Kepadatan Populasi dan Pola Sebaran Teripang (Holothuroidea) di Perairan Pantai Tuhaha Pulau Saparua Kabupaten Maluku Tengah - Fresylia Ribka Louhenapessy; Handy Erwin Pier Leimena; La Eddy (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Sea cucumbers (Holothuroidea) are marine organisms of high ecological and economic value, yet their populations in many tropical regions have declined due to exploitation pressures. This study aimed to analyze the density and distribution patterns of sea cucumbers in the coastal waters of Tuhaha, Saparua Island, Central Maluku Regency. A quantitative descriptive survey was conducted using 1 × 1 m quadrat transects along eight transect lines perpendicular to the shoreline. Density was calculated based on the number of individuals per unit area, while distribution patterns were determined using Morisita’s index. Four species of sea cucumbers were identified, namely Holothuria scabra, Holothuria atra, Bohadschia vitiensis, and Bohadschia marmorata, with a total of 33 individuals and an overall density of 0.19 ind/m². Species H. scabra exhibited the highest density (0.11 ind/m²), whereas H. atra and B. vitiensis had the lowest (0.01 ind/m²). The population distribution was aggregated (Id = 6.11), indicating a strong association with specific microhabitats, particularly muddy-sand substrates. Environmental parameters (temperature 30°C, salinity 30 ‰, pH 6.90) remained within the optimal tolerance range for sea cucumbers. These findings indicate that Tuhaha waters continue to support Holothuroidea populations; however, the aggregated distribution pattern reflects vulnerability to overexploitation. Therefore, ecosystem-based management through habitat conservation, catch restrictions, and the integration of aquaculture and restocking is essential to ensure the sustainability of sea cucumber resources in Central Maluku.